IMPLEMENTASI KEBIJAKAN OTONOMI DAERAH TERHADAP LAJU PEMULIHAN EKONOMI PASCA COVID 19 DI WILAYAH SUMUT - Sinta Aulia Haikal; Marliyah Marliyah (Jurnal Akuntansi AKTIVA, 2023)
This study aims to look at the implementation (role) and policies set by the North Sumatra regional government on several issues related to the Covid-19 virus, one of which is the decline in the regional economy and what steps the government has taken in terms of restoring the economy. The method used in this study is to use an analytical descriptive approach, while the data used are analytical qualitative data sourced from secondary data from the LKPJ Gubernur North Sumatera 2020 and primary data from valid references. Based on the results of the discussion in the implementation of regional autonomy policies on economic recovery, the regional government of North Sumatra and the Pemko Medan have implemented several strategic policies that can be implemented related to fiscal and monetary which are needed to provide stimulation for economic recovery. In addition, the Pemko Medan has also implemented policies to increase economic growth, one of which is collaborating with the North Sumatran Chamber of Commerce (KADIN) for the revival of UMKM as the backbone of regional development.